PENGARUH LITERASI DIGITAL DAN INOVASI PRODUK TERHADAP KINERJA UMKM DENGAN ENTREPRENEURSHIP ORIENTATION SEBAGAI VARIABEL MODERASI (STUDI PADA UMKM KOTA MEDAN) DALAM SEKTOR USAHA MAKANAN - Juna, Shelvy Ali; Purba, Mas Intan; Karisma, Payeel; Chang, Steven; Lubis, Nurul Wardani (POLITEKNIK LP3I JAKARTA, 2026)
Small and Medium Enterprises (SMEs), particularly in the food sector, play an important role in the economy of Medan City. However, although digital adoption is already high, its utilization remains suboptimal, resulting in no significant improvement in performance. This study highlights that digital literacy and product innovation influence SME performance, but their effectiveness is strongly affected by Entrepreneurship Orientation (EO), which includes proactive, innovative, and risk-taking attitudes. EO acts as a strengthening factor that helps SMEs maximize the use of technology and innovation to enhance competitiveness and performance. Unlike previous studies that used digital marketing as a mediating variable, this study positions EO as a moderating variable that determines the extent to which digital literacy and product innovation affect SME performance. The population in this study consists of 125 food-sector SME actors registered and actively operating in Medan Area District, Medan City. This study employs a Simple Random Sampling technique to ensure that each member of the population has an equal chance of being selected as a sample, thereby making the data more representative. The findings indicate that digital literacy has a positive and significant effect on the performance of food-sector SMEs in Medan City, while product innovation does not significantly affect performance. Both digital literacy and product innovation have a positive and significant effect on entrepreneurship orientation, which in turn also has a positive and significant effect on SME performance. Furthermore, entrepreneurship orientation is proven to strengthen the influence of digital literacy on SME performance, but it does not strengthen the influence of product innovation on the performance of food-sector SMEs in Medan City.